End-of-Treatment FDG PET-CT (EOT-PET) in Patients with Post-Chemotherapy Masses for Seminoma: Can We Avoid Further Intervention? - Joel, Anjana; Singh, Ashish; Hepzibah, Julie; Devasia, Antony; Kumar, Santosh; Gnanamuthu, Birla Roy; Chandramohan, Anuradha; George, Arun Jacob Philip; John, Nirmal Thampi; Yadav, Bijesh; John, Ajoy Oommen; Georgy, Josh Thomas; John, Subhashini; Chacko, Raju Titus (South Asian Journal of Cancer, 2022)
Context Patients with seminoma present with advanced disease. End-of-treatment (EOT) positron emission tomography-computed tomography (PET-CT) is done to assess response and direct management of post-chemotherapy residual masses.Purpose This article assesses the utility of EOT PET-CT in the management of post-chemotherapy residual lymph nodal masses seminoma.Materials and Methods We analyzed all patients with seminoma who underwent an EOT PET-CT from January 2015 to January 2020 at our center and calculated the positive predictive value (PPV) and negative predictive value (NPV) of EOT PET-CT in the entire cohort of patients and among subgroups.Results A total of 34 male patients underwent EOT PET-CT. Fourteen (41.2%) were stratified as good risk and 20 (58.8%) as intermediate risk. The median follow-up was 23 months (interquartile range: 9.75–53 months). In 23 patients there were residual masses of size more than 3 cm at the EOT PET scan. EOT PET was positive as per the SEMPET criteria in 18 (78%) out of 23 patients. None underwent retroperitoneal lymph node dissection. All four who underwent image-guided biopsy, showed only necrosis on pathology. One patient with positive mediastinal node (standardized uptake value 13.6) had granulomatous inflammation. There was no relapse or progression during this period of follow-up. The NPV for EOT PET-CT for the entire cohort, > 3 cm, and > 6 weeks cutoff were 100%, respectively. The PPV for EOT PET-CT for the entire cohort, > 3 cm residual mass, and > 6 weeks cutoff were 8.7, 11.11, and 6.67%, respectively.Conclusion EOT PET-CT has a low PPV and high NPV in predicting viable tumor in post-chemotherapy residual masses among patients with seminomatous germ cell tumors. If required, EOT PET positivity can be confirmed by a biopsy or reassessed with a repeat PET-CT imaging to document persistent disease prior to further intervention.
Keywords: seminoma; PET-CT; germ cell tumor; post-chemotherapy residual masses